Liver biopsy and prognosis in acute liver failure. Issue 12 (December 1973) - Scotto, J.; Opolon, P.; Étévé, J.; Vergoz, D.; Thomas, M.; Caroli, J.
Abstract : Liver biopsy was performed in 38 patients with fulminant hepatitis and coma and repeated in 22. Stereological estimation of hepatocyte volume was correlated with levels of clotting factors. Early liver biopsy allowed prognosis in 55% of the cases. All patients with a hepatocyte volume of <35% and thromboplastin time ≤10% died; all patients but two with hepatocyte volume ≥35% and thromboplastin time >10% recovered consciousness (n = 9) or at least showed evidence of marked liver regeneration (n = 2). On serial liver biopsy a significant increase in hepatocyte volume and clotting factors was only observed in patients who recovered consciousness. The estimated liver cell mass after regeneration in patients who recovered consciousness was ≥45% and <45% in the patients who did not.